100 climate actions from cities in Asia and the Pacific. (Manila Asian Development Bank, 2021)
The climate actions are drawn from multiple sectors renewable energy, carbon finance, transport, land use, information and communication technology, climate action plans, building energy efficiency, solid waste management, sustainable and low carbon communities, and climate resilience. The examples show how city-level initiatives contribute to reducing greenhouse gas emissions and building resilience, all while delivering economic, environmental, health, and social co benefits.
Keywords: Renewable energy sources; Climatic change -- Government policy; Electronic books